Depression, anxiety and stress among undergraduate students in IIUM, Kuantan Campus - Ramli, Farizah; Abdul Razak, Hannah; Sajuni, Noor Aisyah; Yaacob, Munirah; Harun, Nor Asilah (2015)
To assess the prevalence of depression, anxiety and stress and identify their associating factors among Kulliyyah of Dentistry (KOD), Kulliyyah of Allied Health Sciences (KAHS) and Kulliyyah of Sciences (KOS) students at International Islamic University Malaysia. Methods: A cross-sectional study was conducted among 476 volunteered students. Their socio-demogrpahic data, self-reported depression, anxiety and stress (DASS-21) score, causes and relieving factors were collected using validated semi-structured pre-tested questionnaires. The data was analysed using Binomial and multiple linear regression tests with SPSS version 16. The prevalence of depression, anxiety and stress was 43.1%, 73.3% and 39.3% respectively. Binomial test indicated that KOD, KAHS and KOS students were significantly experiencing anxiety symptoms (p=0.001). The regression models for depression explained that first and fourth year students were less prone to have depression symptoms. The common predictors associated with all the assessed psychological morbidity were personal factors, while academic factors were related with anxiety and stress symptoms. The highest response for relieving factors factors was spiritual activities (91.2%), followed by sleeping (79.8%) and doing excercise/playing sports (74.6%), while seeking professional help relieved depression, anxiety or stress the leafs (26.5%). This study suggests that anxiety symptoms are prevalent among dental, allied health and sciences students. Hence, it is vital that educational institutions continually evaluate the psychological health of their students and tailor preventive measures and treatment programs to specifically target their needs.